Design of four-bar mechanism for vibratory tillage cultivator using five precision position method for path generation problem. (16th November 2021) - Rao, N.R.N.V. Gowripathi; Kumar, Abhijeet; Chaudhary, Himanshu; Sharma, Ajay Kumar
Agriculture is the backbone of the Indian economy. There are different agricultural operations that play a critical role in overall crop development. Farmers are in search of sustainable technologies that can contribute to their overall economy and improve efficiency. The paper deals to design a vibratory cultivator that saves the time and energy for the farming community. A four-bar mechanism is designed and developed to vibrate the cultivator. A proper analytical synthesis procedure is adopted, such as five precision position method for a particular vibratory tillage trajectory available from the literature. The dimensions of the four-bar mechanism are validated through MATLAB, and it is confirmed that the designed four-bar mechanism traces the path accurately for vibratory tillage operation.